Coping with a Money Crunch: Values, Goals, and Standards - Katey Walker; Josephine Turner; Michael S. Gutter (EDIS)
Revised! FCS-7006, a 3-page illustrated fact sheet by Josephine Turner, Katey Walker, and Michael S. Gutter, helps people experiencing a financial crisis decide on goals and set priorities. Published by the UF Department of Family Youth and Community Sciences, March 2009.